The marine organism toxicity and regulatory policy of brominated flame retardants: a review - Zhang, Weibin; Chen, Yutong; Wang, You; Cao, Sai (Frontiers in Marine Science, 2025)
Brominated flame retardants (BFRs) represent the most widely produced and utilized organic flame retardants globally. Compared to terrestrial and freshwater organisms, research on the marine ecotoxicity of BFRs has lagged behind, with no comprehensive review currently synthesizing these studies. Internationally, BFRs have been subjected to regulatory restrictions due to their demonstrated characteristics as persistent organic pollutants. Nevertheless, significant regulatory gaps persist in current BFRs governance frameworks. Addressing this knowledge gap, this paper briefly reviews the distribution of BFRs in the marine environment, while comprehensively reviewing and comparing their toxic effects on marine organisms and summarize toxic mechanisms. Meanwhile, the paper systematically examines global regulatory policies governing BFRs across various nations and proposes recommendations for enhanced regulatory oversight and legislative improvements. Currently, the studies on the marine biological toxicity of three traditional BFRs, namely polybrominated diphenyl ethers (PBDEs), hexabromocyclododecane (HBCD), and tetrabromobisphenol A, are relatively comprehensive. These BFRs can exert various toxic effects on planktonic, benthic, and nektonic organisms, mainly including growth and development toxicity, reproductive toxicity, immunotoxicity, and neurotoxicity. However, the toxicity studies on novel BFRs, such as decabromodiphenyl ethane, are scarce and urgently need to be initiated. Moreover, researches on the marine biological toxicity mechanisms of BFRs are relatively simplistic, lacking in the characteristics of different BFRs and adverse outcome pathways starting from the molecular level. Within existing global regulatory frameworks, PBDEs, HBCD, and hexabromobiphenyl have been comprehensively prohibited and phased out. However, environmental risk assessments for alternative BFRs remain ongoing, with corresponding legislative actions lagging behind scientific findings.